1999
DOI: 10.1039/a905214c
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of liquid tetramethylurea and its aqueous solution

Abstract: Thermodynamic properties and correlation functions for the pure liquid 1,1,3,3-tetramethylurea (TMU) and its aqueous solution were obtained by Monte Carlo simulation in the isothermic and isobaric (NPT) ensemble at 25 ¡C and 1.0 atm. An eight site potential model combining Lennard-Jones plus coulombic functions was developed to calculate intermolecular interaction between TMU molecules. In this model the methyl groups are represented by a united atom approach. The partial charges needed for Coulomb interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
1
32
0
4
Order By: Relevance
“…33 Consequently, the long-range electrostatic contribution to the electrostatic energy is lower than could be expected for a strictly Coulombic system. This is in accord with recent results 34 using the generalised Born model. 35,36 Also in good agreement with this, it is observed that site-site pair correlation functions, thermodynamic properties and single particle dynamics of polar liquids, appears to be quite insensitive to the long-range forces in the system.…”
Section: Monte Carlo Simulationssupporting
confidence: 82%
“…33 Consequently, the long-range electrostatic contribution to the electrostatic energy is lower than could be expected for a strictly Coulombic system. This is in accord with recent results 34 using the generalised Born model. 35,36 Also in good agreement with this, it is observed that site-site pair correlation functions, thermodynamic properties and single particle dynamics of polar liquids, appears to be quite insensitive to the long-range forces in the system.…”
Section: Monte Carlo Simulationssupporting
confidence: 82%
“…However, there is a possibility that a TMU molecule interacts with another TMU molecule through dipole-dipole interactions [12,13,15]. In the case of dissolution of TMU in an alkanol, the breaking of hydrogen bonding among alcohol molecules and that of intermolecular dipole-dipole interactions in the pure solute take place [18].…”
Section: Discussionmentioning
confidence: 99%
“…MeOHÞ is negative only in the case of unsubstituted U, whereas TMU has a substantially more positive value of D tr H m than the other methyl-substituted ureas. The difference between standard molar enthalpies of solution of TMU in water ðD sol H m ffi À22: 19 Interest in solutions of TMU is due not only to peculiarities of its hydration (solvation) but also, like U, to biochemical importance of such systems [7][8][9][10][11][12][13][14][15]. Besides TMU has some unique properties among the ureas.…”
Section: Introductionmentioning
confidence: 99%
“…Microheterogeneities of the binary solvent media, leading to an inversion in the configuration of the liquid mesodomains, were found to be decisive for the onset of protein gelation [14][15][16]. From an academic point of view, such systems are very interesting models for investigating the driving forces involved in protein folding/unfolding and selfassembly events.…”
Section: Introductionmentioning
confidence: 97%